ACCOUNTING OF CAPITAL RESERVES AS A RISK MANAGEMENT TOOL FOR PROTECTING THE CAPITAL OF THE ENTERPRISE - Ольга Грицай; Natalia Voskalo; Volodymyr Voskalo; Yuliia Demska; Ihor Defir (Фінансово-кредитна діяльність: проблеми теорії та практики, 2024)
The activities of business entities are conducted in conditions of uncertainty, which leads to the emergence of various types of business risks. The accounting system plays an important role in the information provision of risk management. Reliable accounting data can be a reliable source of information when making decisions on economic risk management both by the managers of the enterprise and by other parties interested in its activities. The article is devoted to the study of the accounting provision of capital reserves as a risk management tool for the protection of the capital of the enterprise. In the classification of capital reserves, an additional feature is distinguished by the identification of risks for the management of which the reserves are formed. It has been established that the risks of enterprises are the subject of the formation of reserves, and therefore it is advisable for the enterprise to create specific types of reserves that are necessary to cover the types of risks that are inherent in its activities.